Surveillance, prevention and control of vector-borne infections - Day, Jonathan (Henry Stewart Talks, 2010)
Vector-borne disease surveillance, Pathogen detection, Spatial distribution of vector-borne diseases, Temporal distribution of vector-borne diseases, Measurement of vector-borne disease transmission risk, Vector-borne disease prevention, Vector avoidance, vector control, and disease control
Updated at 2014/10/01, Archived at 2021/11/28